ESCMID∗ guideline for the diagnosis and treatment of biofilm infections 2014. (1st May 2015) - Høiby, N.; Bjarnsholt, T.; Moser, C.; Bassi, G.L.; Coenye, T.; Donelli, G.; Hall-Stoodley, L.; Holá, V.; Imbert, C.; Kirketerp-Møller, K.; Lebeaux, D.; Oliver, A.; et al.
Abstract: Biofilms cause chronic infections in tissues or by developing on the surfaces of medical devices. Biofilm infections persist despite both antibiotic therapy and the innate and adaptive defence mechanisms of the patient. Biofilm infections are characterized by persisting and progressive pathology due primarily to the inflammatory response surrounding the biofilm. For this reason, many biofilm infections may be difficult to diagnose and treat efficiently. It is the purpose of the guideline to bring the current knowledge of biofilm diagnosis and therapy to the attention of clinical microbiologists and infectious disease specialists. Selected hallmark biofilm infections in tissues (e.g. cystic fibrosis with chronic lung infection, patients with chronic wound infections) or associated with devices (e.g. orthopaedic alloplastic devices, endotracheal tubes, intravenous catheters, indwelling urinary catheters, tissue fillers) are the main focus of the guideline, but experience gained from the biofilm infections included in the guideline may inspire similar work in other biofilm infections. The clinical and laboratory parameters for diagnosing biofilm infections are outlined based on the patient's history, signs and symptoms, microscopic findings, culture-based or culture-independent diagnostic techniques and specific immune responses to identify microorganisms known to cause biofilm infections. First, recommendations are given for the collection of appropriate clinical samples, for reliable methods to specifically detect biofilms, for the evaluation of antibody responses to biofilms, for antibiotic susceptibility testing and for improvement of laboratory reports of biofilm findings in the clinical microbiology laboratory. Second, recommendations are given for the prevention and treatment of biofilm infections and for monitoring treatment effectiveness. Finally, suggestions for future research are given to improve diagnosis and treatment of biofilm infections.